Calcareous sponges from the French Polynesia (Porifera: Calcarea) - Klautau, Michelle; Lopes, Matheus Vieira; Guarabyra, Bruna; Folcher, Eric; Ekins, Merrick; Debitus, Cécile (Zootaxa, 2020)
Although the French Polynesian reefs are among the most well studied reefs of the world, sponges are still poorly known, with only 199 species or OTUs of sponges having been described from French Polynesia, 167 at an OTU level and 32 at a species level. From those 199 species, just five are calcareous sponges. As it is possible that this number is underestimated, the aim of the present work was to study the diversity of calcareous sponges from French Polynesia. Hence, different French Polynesian archipelagos were surveyed by SCUBA from 3 to 60 m of depth. Identifications were performed using morphological and molecular (ITS and C-LSU) tools. We found a total of nine species of Calcarea, comprising five different genera. Five species are new to science: Clathrina fakaravae sp. nov., Clathrina huahineae sp. nov., Ernstia variabilis sp. nov., Leucascus digitiformis sp. nov., and Leucandra tahuatae sp. nov. With the present work, the number of identified sponges from French Polynesia at a species level increased from 32 to 41. The only calcareous sponge previously known from French Polynesia that was recollected by our group was Leucetta chagosensis. Our results suggest that the Eastern Indo-Pacific Realm shows more affinity with the Central and the Western Indo-Pacific Realms. Four species supported these affinities: Ascandra cf. crewsi, previously known only from Papua New Guinea, Leucascus simplex from South Australia, and Leucetta chagosensis and L. microraphis, both widespread species in the Indo-Pacific. These two Leucetta species, however, most likely represent species complexes. Once again the molecular markers ITS and C-LSU helped in the identification of calcareous sponges, showing how important is an integrative taxonomy. Although our work has increased in 250% (6 spp to 15 spp) the diversity of calcareous sponges in French Polynesia, it is most possible that this number is still underestimated.